Water for food as food for thought: case study of applying the PODIUMSim model to Uzbekistan - Yakubov, Murat; Manthrithilake, Herath (Wiley, 2009)
Uzbekistan, being historically one of the most populated and agriculture-based republics in the former Soviet Union, still features quite high annual population growth rates and great dependence on agriculture as a backbone for the rest of the economic reforms.With water playing an extremely important role in producing a sufficient food base for the country's growing population and earning much needed foreign exchange for the government to ensure overall economic development, the pressures on this scarce resource will obviously and inevitably grow, putting it much at risk over a long-term perspective. So would available water be enough to meet ever-increasing demands from major economic uses in the foreseeable future, and what can be the options for meeting such demands - these are the key questions raised and researched in this article. As such the research concentrates on the two major country-specific scenarios with water and its multiple uses for Uzbekistan - the business as usual and the best case. Both scenarios discuss possible future implications for the next quarter-century given certain assumptions. Finally when summarizing the findings, the paper provides conclusions and recommendations as to how the model and further scenarios can be better optimized given the trans-boundary nature of most water resources in Central Asia where Uzbekistan geographically belongs.